The genetic diversity of genogroup I noroviruses causing acute gastroenteritis outbreaks in Beijing between 2014 and 2023 - Xiangyu Hu; Lingli Sun; Taoli Han; Jianhong Zhao; Xiao Qi; Yue Zhang; Pan Lu; Jiaxin Zhao; Yan Gao; Zheng Zhang; Beibei Li; Jialiang Du; et al. (Heliyon)
Background: In the past decade, we have continuously conducted sporadic monitoring and outbreak detection of norovirus (NoV), which causes human acute gastroenteritis (AGE) in the capital of China. Accumulated data have shown that genogroup I (GI) NoVs not only cause sporadic cases but also cannot be ignored during outbreaks. This study aimed to update the genetic diversity of GI NoVs in the capital of China from 2014 to 2023. Methods: Fecal or anal swab samples were collected from AGE outbreaks triggered by GI NoVs in Beijing Chaoyang District from 2014 to 2023. Both the partial coding genes of RNA-dependent RNA polymerase (RdRp) (∼283 bp) and viral protein 1 (VP1) (∼303 bp) were amplified via reverse transcription polymerase chain reaction (RT-PCR) and sequenced, followed by genotyping and phylogenetic analysis. Results: A total of 421 fecal or anal swab samples were collected from 59 AGE outbreaks caused by GI NoVs. Genetic diversity was observed, with nine genotypes reported, including recombinant strains of GI.6[P11] and GI.3[P13], as well as multiple subtypes that cocirculated. In addition, we also reported a shift in the dominant genotype, with GI.6 [P11] in 2015–2018, GI.3 [P13] in 2019–2021, and GI.4 [P4] in 2023. Furthermore, alterations in amino acids were indirectly indicated through single nucleotide polymorphisms (SNPs) in certain VP1 areas of strains GI.3[P13] and GI.6[P11]. Epidemiologically, the peak of infection induced by GI NoVs occurs from March to May. Conclusions: The sustained circulation and obvious genotype shift of GI NoVs in this region cannot be ignored, and GI.4[P4] NoVs are highly likely to become the main epidemic strain in the following years.